2016
DOI: 10.1213/ane.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Transversus Abdominis Plane Block for Postoperative Analgesia in Patients Undergoing Total Laparoscopic Hysterectomy: A Randomized, Controlled, Observer-Blinded Trial

Abstract: TAP block did not reduce morphine consumption during the first postoperative 24 hours after elective total laparoscopic hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 15 publications
3
59
1
Order By: Relevance
“…There was no clinically significant difference in median maximal pain scores in the immediate postoperative period, but the liposomal bupivacaine group had decreased maximum pain scores, decreased opioid use, and a lower incidence of PONV for the first 24 hours 39. Ghisi and coworkers40 compared ultrasound-guided TAP block with systemic opioid analgesia and found no advantage in terms of VAS score, opioid consumption, postoperative mobilization, or adverse events. Finally, Guardabassi and colleagues41 found no advantage in terms of opioid consumption during the first 24 hours, and no difference in pain scores, when TAP blocks were added to a systemic analgesia regimen including opioid PCA.…”
Section: Resultsmentioning
confidence: 97%
“…There was no clinically significant difference in median maximal pain scores in the immediate postoperative period, but the liposomal bupivacaine group had decreased maximum pain scores, decreased opioid use, and a lower incidence of PONV for the first 24 hours 39. Ghisi and coworkers40 compared ultrasound-guided TAP block with systemic opioid analgesia and found no advantage in terms of VAS score, opioid consumption, postoperative mobilization, or adverse events. Finally, Guardabassi and colleagues41 found no advantage in terms of opioid consumption during the first 24 hours, and no difference in pain scores, when TAP blocks were added to a systemic analgesia regimen including opioid PCA.…”
Section: Resultsmentioning
confidence: 97%
“…Also Ghisi et al [40] found that, TAP block did not reduce morphine consumption during the first postoperative 24 h after elective total laparoscopic hysterectomy.…”
Section: Discussionmentioning
confidence: 96%
“…Recent randomized controlled studies (2011 ~ current) on the analgesic effect of single-shot TAP block after laparoscopic lower abdominal surgery are shown (Table 3) 7-10, [12][13][14][15][16][17][18][19] . Although a meta-analysis including these investigations suggested that TAP block reduces perioperative opioid consumption 20 , NRS was decreased in only 4 of those 12 studies.…”
Section: Discussionmentioning
confidence: 99%